Standardization of Kesambi Leaf Extract (Schleichera oleosa) from The Selayar Area: Standardisasi Ekstrak Daun Kesambi (Schleichera oleosa) yang Berasal dari Daerah Selayar - Afra Azisah Azisah; Alfrida Monica Salasa; St. Ratnah (Akademi Farmasi Surabaya, 2023)
Kesambi leaves are part of plant that’s commonly used as medicine, at Selayar district. In general, the monograph of a medicinal plant is listed in Indonesian Herbal Pharmacopoeia, but kesambi leaves haven’t been included in the book so standardization needs to be carried out. The purpose of this study is to determine the standard values of specific and non-specific parameters of Kesambi (Schleichera oleosa) leaf extract originating from the Selayar. The majority of testing methods refer to the standardization book issued by the Indonesian Ministry of Health. The results of the specific parameters of Kesambi Leaf extract are blackish brown, characteristic odor and thick taste. The total level of flavonoids was 1.2918% b/b and polyphenols were 9.738% b/b. Compounds dissolved in ethanol were 13.1866 ± 1.5894 and in water were 13.9474 ± 0.1561. Testing non-specific parameters obtained drying shrinkage of 33.4307 ± 5.7692, water content 5.1797 ± 0.5462, total ash content 2.5178 ± 0.2559, acid insoluble ash content 0.4394 ± 0.2906, as well as microbial contamination and heavy metal contamination that comply with the requirements.